Politiķu - administrācijas attiecības Latvijas pašvaldībās (Tukuma un Talsu gadījums) - Zviedris, Artūrs (Latvijas Universitāte, 2017)
Bakalaura darbā ”Politiķu – administrācijas attiecības Latvijas pašvaldībās (Tukuma un Talsu gadījums)” pētītas pašvaldību politiķu un pašvaldības administrācijas attiecības par pamatu ņemot ASV politikas zinātņu profesora Dž.H.Svara pašvaldības domes un pašvaldības domes vadītāja teorētiskos modeļus. Pētījuma mērķis: izpētīt pašvaldību politiķu un administrācijas attiecības Latvijas pašvaldībās. Pētījuma objekts: pašvaldības deputātu un administrācijas tiesiskās attiecības. Pētījuma priekšmets: pašvaldību politiķu un administrācijas attiecības Tukuma un Talsu novadā. Pētījuma jautājums: kā teorētiski Latvijā darbojas pašvaldības politiķu un administrācijas attiecību modeļi? Pētījumā izmantoti 77 avoti, darba apjoms 58 lpp.

Theme of this bachelor thesis is „Interaction between politicians and administration in municipalities of Latvia (Cases of Tukums and Talsi municipalities)” The author has examined interaction between politicians and administration in municipalities, using theoretical model of interaction between politicians and administration, formulated by US professor of political science J.H. Svara. Aim of this thesis is to examine interaction between politicians and administration in municipalities of Latvia. Object of this thesis is legal relations between employees and deputies of municipality. Subject of this thesis is relations between employees and deputies in municipalities of Tukums and Talsi. Question of this thesis is how in Latvian operates theoretical model of interaction between politicians and administration? There are 77 sources used. Scope of this paper is 58 pages. Key
Interaction between politicians and administration in municipalities of Latvia (Case of Tukums and Talsi municipalities)
Keywords: Politikas zinātne (politoloģija); pašvaldības dome; pašvaldības administrācija; deputāts; pašvaldības darbinieks